TRANSLATION AND VALIDATION OF THE AMSTERDAM PREOPERATIVE ANXIETY AND INFORMATION SCALE (APAIS) INTO HAUSA LANGUAGE - Dagona, Sabo Saleh; Archibong, Uduak; McClelland, Gabrielle Tracy (PEOPLE: International Journal of Social Sciences, 2019)
Objectives: The objectives of this study ware to translate and validate the Amsterdam Preoperative Anxiety and Information Scale into Nigerian Hausa Language to be used in assessing Hausa speaking surgical patients’ preoperative anxiety before undergoing elective surgery. Methods: Forward and backward translation method was adopted to translate APAIS into Hausa Language so as to produce a Hausa version of the scale (APAIS-H). The Hausa version was tested on thirty patients scheduled for elective surgery at Federal Medical Centre, Nguru-Yobe State, Nigeria. The authors performed factor analysis, internal consistency and correlated the translated Hausa version with Spielberger’s State Trait Anxiety Inventory (STAI-State). Findings: The translated Hausa version of the scale produced high internal consistency for the two subscales (Cronbach’s alpha 0.82 for anxiety related to surgery subscale and 0.71 for information desire subscale respectively). APAIS-H correlated well with Spielberger’s state Trait Anxiety Inventory STAI-state with a correlation coefficient of (r = 0.81), Conclusion: APAIS-H has been found to be valid and reliable instrument to be used in the assessment of preoperative anxiety in Hausa speaking patients scheduled to undergo surgical operation.